Duo cum faciunt idem, non est idem: Evidence from Austrian pain and suffering verdicts - Andrea Leiter; Magdalena Thöni; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2011)
We analyze the pricing of pain and suffering and, in particular, whether the corresponding compensations are affected by a court's approach to value such damages. For this purpose, we use data on pain and suffering verdicts in Austria, where courts are generally free to choose between a per diem and a lump sum scheme to assess payments on damages for pain and suffering. We find significant higher payments under the lump sum regime, which are not vanishing even after controlling for individual- and injury-specific characteristics. Our evidence suggests that the observed difference between lump sum and per diem schemes mainly appears if the victims are female and exposed to multiple injuries and, to a lesser extent, to intensive past pain days.
Keywords: K13; K41; 330; Tort Law; Per Diem Pain and Suffering Damages; Lump Sum Pain and Suffering Damages